EdTech and public policies: Introducing the question - Valle, Lilian do; Mill, Daniel; Victorio Filho, Aldo (Education Policy Analysis Archives, 2018)
It has become a commonplace if not a truism to assert that the unprecedented development of digital technologies has radically changed our lives. However, the rapidity with which technical possibilities multiply does not seem to be accompanied by the constant examination, by the creation and re-creation of the ends to which those means must be subject, especially in the field of education. For there is no reason to imagine that the “spontaneous socialization” promoted by simple access to the network does not follow the colors of conformity that prevail in our societies. For this reason, the main objective of this dossier is to contribute to the criticism of the discourses and representations that rules our daily life with technology, naturalizing the logics that should be the subject of our careful evaluation, in order to open the way to the invention of practices, policies, and programs of distance education that, renewing the uses of technology, point out to us new perspectives for the democratic formation of the citizens.